Voltage-controlled reactive magnetron sputtering of Nb-doped TiO2 films: electrical and optical properties. Issue 46 (28th April 2016) - Seeger, Stefan; Ellmer, Klaus; Weise, Michael; Reck, Johanna; Mientus, Rainald
ABSTRACT: Niobium-doped TiO2 films as highly transparent conducting oxidic electrodes were prepared by reactive magnetron sputtering from a titanium target in an argon-oxygen gas flow. As-deposited films were amorphous and exhibited high resistivities ranging from 10 to 1×10 5 Ω cm in dependence on the deposition parameters. We stabilized the reactive magnetron sputtering deposition by adjusting the magnetron discharge voltage at a constant oxygen gas flow. The precise process control during the preparation of the as-deposited films was essential to gain low resistivities (10 -3 Ω cm) and low optical absorption coefficients (α550nm < 2×10 3 cm -1 ) after annealing. These polycrystalline TiO2 :Nb films on borosilicate glass show a quite high electron concentration > 1×10 20 cm -3 and a high carrier mobility (≈ 8 cm 2 V -1 s -1 ).